Impact of educational differences as measure of socioeconomic status on survival for breast cancer patients - Nowara, Elżbieta; Suwiński, Rafał (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : Breast cancer is the most frequent malignancy affecting women. Some reports suggest the influence of socioeconomic status, including education, on survival rates for cancer patients. This report analyzes the effect of patients’ education level on their survival. Material and methods : A retrospective analysis of the group of 810 breast cancer patients treated in single center in Poland was performed. The analyzed group included women with elementary education (24%), vocational training (19%), secondary (38%) or higher education (16%). Overall, recurrence-free and metastasis free survival times were analyzed. Results: The actuarial 5-year overall survival was 72% (median 4.7 years), 5-year local recurrence-free survival was 84%, whereas metastasis-free survival 76%. Multivariate Cox model has shown that lower education had independent significantly negative influence on local recurrence-free survival time (p = 0.024). The highest risk of recurrence was found for patients with elementary education (p = 0.009). The same was confirmed for distant metastasis-free survival (p = 0.001), with the highest risk of metastases in patients with vocational education and stage IIIB breast cancer (p < 0.001). Education level had significant impact on overall survival. The patients with higher-level education lived longer (p = 0.042). Conclusions : Shorter recurrence-free survival time among women attaining lowest education level and longer overall survival time for women with higher education level suggest the necessity for intensified cancer awareness educational effort and screening among less-educated healthy Polish women.